(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to assess and determine social media marketing as a promotional strategy for fast-food restaurants in terms of entertainment, interaction, trendiness, and customization. The respondents who experienced problems are not far from the number of respondents who didn’t experience probleMs. The problems that were observed and experienced by the respondents were correlated to the highlighted variables. This study recommended that restaurant operators should consider implementing social media marketing activities to create an atmosphere of trust and credibility that will encourage customers to share their experiences with others. Restaurant marketers and operators should strive to create positive online reviews and ratings by encouraging customers to share their experiences online. The researchers highly recommend that future researchers seek further to improve the whole process and come up with another study to ensure the gratification of customers to the social media marketing strategy of fast-food restaurants. The fast-food restaurants should adopt responses cited by respondents and conduct further regular surveys or interviews regarding customers' preferences and suggestions that should be utilized to improve their social media marketing strategies.